(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the profound effects of virtual tourism in the present period of technological progress, with a specific emphasis on its impact on persons’ inclinations to travel. The objective of the study is to comprehend the link between virtual tourist experiences (VTE), electronic word-of-mouth (e-WOM), and visit intentions (VIN). The study employed a quantitative approach, using structured questionnaires and analysing the data with the SPSS macro PROCESS. The results highlight the beneficial effects of Virtual Tourism Experiences on electronic Word-of-Mouth and Virtual Influencer Networks, emphasising the significance of genuine virtual interactions in shaping traveller intentions. The study emphasises the importance of electronic word-of-mouth (e-WOM) as a critical mediator, underscoring the necessity for strategic communication endeavours to cultivate favourable impressions. Moreover, acknowledging the role of e-WOM susceptibility as a mediator highlights the significance of customising communication techniques to cater to various audience preferences. These insights provide destination marketers significant advise on investing in sophisticated virtual infrastructure, harnessing social influence, and actively controlling the virtual destination image.